2017
DOI: 10.1186/s13195-017-0237-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for benefit of statins to modify cognitive decline and risk in Alzheimer’s disease

Abstract: BackgroundDespite substantial research and development investment in Alzheimer’s disease (AD), effective therapeutics remain elusive. Significant emerging evidence has linked cholesterol, β-amyloid and AD, and several studies have shown a reduced risk for AD and dementia in populations treated with statins. However, while some clinical trials evaluating statins in general AD populations have been conducted, these resulted in no significant therapeutic benefit. By focusing on subgroups of the AD population, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
133
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(147 citation statements)
references
References 65 publications
9
133
0
5
Order By: Relevance
“…Studies have indicated a connection between the ApoE4 allele on the apolipoprotein gene with hypercholesterolemia and increased risk of development of Alzheimer's disease [16]. Greater than 50% of subjects participating in clinical trials of Alzheimer's disease are positive for ApoE4 [17]. Similarly, two meta-analyses have reported a correlation between statin therapy and a reduced risk in the development of Parkinson's disease [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated a connection between the ApoE4 allele on the apolipoprotein gene with hypercholesterolemia and increased risk of development of Alzheimer's disease [16]. Greater than 50% of subjects participating in clinical trials of Alzheimer's disease are positive for ApoE4 [17]. Similarly, two meta-analyses have reported a correlation between statin therapy and a reduced risk in the development of Parkinson's disease [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, statins belong to a class of lipidlowering drugs widely used in the treatment of hyperlipidemia. Based on neurodegenerative disease research, different statins may have a beneficial effect in the treatment of dementia [5], PD [6], and Alzheimer's disease [7].…”
Section: Introductionmentioning
confidence: 99%
“…Proposed explanations for the heterogeneity of any medication effects have included variation in the type of statin [52, 53, 55], genetic background [52], age of intervention [51], degree of cognitive impairment [10], and race/ethnicity and gender [53]. Our findings from a large, population-based sample support a unifying hypothesis – namely, that chronic statin use in mid- to late-life does not appear to impact neuroimaging biomarkers of typical AD but may have the capacity to influence brain structure and function and the resultant risk of dementia through modifying cerebrovascular health.…”
Section: Discussionmentioning
confidence: 99%